2017
DOI: 10.1177/1363460717708147
|View full text |Cite
|
Sign up to set email alerts
|

Everywhere and nowhere simultaneously: The ‘absent presence’ of sexuality in medical education

Abstract: A comprehensive history of medical sex education in the USA is missing from the literature, and much of the recent literature on sexuality education within medical training in the USA relies on survey research, which reveals little about the nature and content of medical sex education, and the meanings of sexuality that are produced and transmitted within it. In this article I provide a brief historical overview of medical sex education in the USA to provide context for my ethnographic study of the ways in whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Sexual and gender minoritized (SGM) individuals and individuals born with a difference in sex development (DSD) experience ongoing health inequities that are, in part, caused by intersecting systems of oppression embedded in health care and medical education. [1][2][3][4][5][6] Despite decades of social changes and developments to include medical education content on people who are SGM and/or born with DSDs, 7 in 2011, a landmark national survey found that medical schools across the United States had few to no content hours on SGM/ DSD medical education. 8 At the time, common barriers to implementing medical education curricula on SGM/ DSD health care included uncertainty of what content to teach and where to include it in the existing curriculum, absence of trained faculty to teach, and lack of resources to teach the content well.…”
Section: Discussionmentioning
confidence: 99%
“…Sexual and gender minoritized (SGM) individuals and individuals born with a difference in sex development (DSD) experience ongoing health inequities that are, in part, caused by intersecting systems of oppression embedded in health care and medical education. [1][2][3][4][5][6] Despite decades of social changes and developments to include medical education content on people who are SGM and/or born with DSDs, 7 in 2011, a landmark national survey found that medical schools across the United States had few to no content hours on SGM/ DSD medical education. 8 At the time, common barriers to implementing medical education curricula on SGM/ DSD health care included uncertainty of what content to teach and where to include it in the existing curriculum, absence of trained faculty to teach, and lack of resources to teach the content well.…”
Section: Discussionmentioning
confidence: 99%
“…However, in fact, sexuality has never been taught in many medical schools. In general, there is reproduction in the medical curriculum but not sexual attitudes [24]. Thus, the attitude towards sex should be included as a specific subject of sexual education or part of reproduction [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Some authors attribute this lack of exploration and research to insufficient training for professionals working with women who have experienced gender violence, in areas such as primary care (Murphy, 2019), education services (Sanabria & Murray, 2018) and national security services and the armed forces (López-Ossorio et al 2018;Menéndez, Pérez & Lorence, 2013), and the limited academic education available in the field of sexuality (Chen & Barrington, 2017). This lack of exploration is striking given that forced sexual activity is a risk factor associated with manslaughter and murder (López-Ossorio et al 2018;Martínez-Sanz, Mañas-Viejo, & Pons-Salvador, 2016).…”
mentioning
confidence: 99%